Preparation And Characterization Of Epoxy Particlefilled Thermosetting Composites - Low , Lay Foon (2012)

(untitled)
Water-based emulsion technique was used in this study to produce hollow epoxy particles (HEP) and solid epoxy particles (SEP). The HEP and SEP fillers were then chemically treated with hydrochloric acid solution to get rid of the excessive calcium carbonate on the surfaces of the fillers. It was found that HEP and SEP fillers could be optimally prepared at the homogenizing time of 9 minutes and 7 minutes, respectively under the homogenizing speed of 15,000 rpm. HEP fillers were added into the epoxy, vinyl ester and polyester thermosetting matrices at different loading amounts (0-9 wt%) to strengthen and toughen the thermosetting matrices. The optimum mechanical properties (i.e., fracture toughness, impact strength, tensile strength, tensile modulus and flexural strength) of the HEP-filled composites could be achieved by the addition of 3, 5 and 5 wt% of the HEP filler content into the epoxy, vinyl ester and polyester matrix, respectively. The strengthening and toughening of the HEP-filled composites involved the interlocking of thermosetting matrices into the pores regions of the HEP fillers. However, the addition of excessive HEP loading into the thermosetting matrices led to the deterioration of the mechanical properties of the composites. This was attributed to the agglomeration of the HEP fillers among themselves, creating stress concentration area. It was also found that the addition of HEP fillers into the thermosetting matrices increased the glass transition temperature, thermal stability, and storage modulus of the composites. The water absorption and diffusion coefficient of the composites also increased with increasing the HEP loading, varying from 0 to 9 wt%.